Cryptotanshinone from Salvia miltiorrhiza Roots Reduces Cytokeratin CK1/10 Expression in Keratinocytes by Activation of Peptidyl-prolyl-cis-trans-isomerase FKBP1A - Esch, Stefan; König, Simone; Bopp, Bertan; Jose, Joachim; Brandt, Simone; Hensel, Andreas (Planta Medica, 2019)
Cryptotanshinone (CTS) (1 µM) from the roots of Salvia miltiorrhiza exerts a strong influence on the terminal differentiation of human keratinocytes (HaCaT cell line, primary natural human keratinocytes) and downregulates the expression of differentiation-specific cytokeratins CK1 and CK10 on protein and gene level. Other differentiation specific proteins as involucrin, filaggrin, loricrin, and transglutaminase were not affected to a higher extent. CTS (1 µM) did not influence the cell viability and the proliferation of keratinocytes. Using a combination of drug affinity response target stability assay in combination with a proteomic approach and multivariate statistics for target elucidation, peptidyl-prolyl-cis-trans-isomerase FKBP1A (known target of inhibitors such as tacrolimus or rapamycin) was addressed as potential molecular target of CTS. The interaction of CTS with FKBP1A was additionally shown by thermal shift and enzymatic activity assays. Interestingly, CTS served as an activator of FKBP1A, which led to a reduced activity of the TGFβ receptor pathway and therefore to a diminished CK1 and CK10 expression. The combination of the FKBP1A activator CTS with the inhibitor tacrolimus neutralized the effects of both compounds. From these data, a potential dermatological use of CTS and CTS-containing plant extracts (e.g., hydroalcoholic extract from the roots of S. miltiorrhiza) for keratinopathic ichthyosis, a disease characterized by overexpression of CK1 and CK10, is discussed. This study displays an experimental strategy for combining phytochemical aspects on active natural products with systematic identification of molecular targets on gene, protein, and cell level.
Keywords: CFKBP1A; cryptotanshinone; differentiation; keratinocytes; Salvia miltiorrhiza; Lamiaceae; TGFβ receptor